THE BADI’ FACE IN SERMON QASS BIN SAIDA AL-IYADI - Nur Halimah, Nafi; Jaida Azizah, Aufa (Journal of Arabic Language and Literature (ALLAIS), 2024)
This article explores the types of verbal escalation found in several sermon Qass bin Sa'ida al-Iyadi. The researcher uses Arabic rhetoric theory as written by Abd al-Rahman Hassan Habankah al-Maidani on the topic "Arab Rhetoric, its Foundations, Science and Art", especially in the Badi' chapter on rhetoric. The way to use this theory is to look for words or sentences that match the sermon with the types written in the book. The method used by researchers in analyzing this research is a qualitative research method by taking a library analysis approach and specifying activities and library materials without requiring field research. The method used to collect data is a method of increasing persistence in research, namely a method that relates to things and variables in the form of writing, images or large works.The results of the analysis of Al-Badi''s face using the rhetorical theory of Al-Badi' Kutbah by Qass bin Sa'ida Al-Ayadi, namely 17 complete anaphora parts, 44 non-tan anaphora parts, 113 assonance parts, 4 balance parts, 31 response parts, sacrum on the chest, 24 from harmony, 2 from hugs, 4 from unnecessary habits, and 1 from the heart or opposite.